ANESTEZJOLOGIA I INTENSYWNA TERAPIAOxycodone: a new alternative in postoperative pain treatment - Misiołek, Hanna; Białka, Szymon; Kucewicz-Czech, Ewa (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Post-thoracotomy pain is one of the most severe types of postoperative pain. It can last up to 2 months and can become chronic in 30% of patients. Pain relief after thoracic surgery is of particular significance, not only for ethical considerations but also for reduction of postoperative pulmonary and cardiac complications. Thoracic epidural analgesia with local anesthe- tics and opioids is regarded as the gold standard treatment for post-thoracotomy pain management because it results in early extubation, better ventilatory mechanisms and gas exchange, decreased incidence of atelectasis, pneumonia and chronic postoperative pain. When epidural analgesia is contraindicated or cannot be performed, other regional or general techniques of analgesia can be used. Opioids are the most popular agents for postoperative pain relief. Oxycodone is a strong opioid agonist which is useful for the management of severe pain. It is becoming increasingly important to assess the relative efficacy and harm caused by different treatments. The paper presents a pharmacological profile of oxycodone and its applicability to relieve severe pain after cardio- and thoracic surgery. Better bioavailability and fewer side effects compared with morphine suggest that oxycodone is an alternative in the treatment of acute pain after thoracotomy.